Moderate and severe adverse events in pediatrics: characteristics of incidents reported during the COVID-19 pandemic - Gabrielli de Oliveira Lima; Ananda Rosa Borges; Victoria Tiyoko Moraes Sakamoto; Julia Rambo Florentino; Anelise Leal Pereira Jardim; Marina Scherer Silveira; Wiliam Wegner (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To verify the characteristics of safety incident reports resulting in moderate and severe harm to pediatric patients in two hospitals during the COVID-19 pandemic. Method: Cross-sectional study conducted in two hospitals in southern Brazil. The sample consisted of 137 notifications from March 2020 to August 2021. The data were collected through the electronic records of the institutions' notification systems and analyzed using descriptive and inferential statistics. Results: The most prevalent incidents were related to clinical processes or procedures (41.6%), affecting slightly more females (49.6%) and infants (39.4%). The majority of incidents (48.2%) occurred in inpatient units. The event sector (p=0.001) and the shift (p=0.011) showed statistically significant associations in both hospitals. Conclusion: The characteristics of the notifications are similar between the institutions surveyed, with a low number of moderate and severe incidents.